Investigating the effects of hydrodynamics and mixing on mass transfer through the free-surface in stirred tank bioreactors. (23rd November 2017) - de Lamotte, Anne; Delafosse, Angélique; Calvo, Sébastien; Delvigne, Frank; Toye, Dominique
Highlights: A stirred tank aerated through the free-surface is globally and locally characterized. PIV and PLIF are used to assess flow, mixing and mass transfer dynamics. Large-scale flow patterns highly influence mass transfer through the free-surface. Mixing efficiency is described based on time stabilization and spatial uniformity. Vertical gradients of dissolved gas concentration are present and persistent. Abstract: In stirred-tank bioreactors, flow structures of various length and time scales are implied in scalar transport phenomena, such as gas species transfer through the liquid free-surface and their homogenization in the bulk. A proper understanding of the underlying mechanisms, i.e. hydrodynamics, mixing and mass transfer, and of their interactions is required to design and develop reliable and efficient production-scale bioprocesses. The objective of the present work is to experimentally investigate the coupling between gas-liquid mass transfer of oxygen with mixing efficiency and circulation patterns inside an arbitrarily chosen stirred-tank configuration aerated through the liquid free-surface, a baffled 20 L-vessel agitated by two Rushton turbines. Based on global parameter values, the most appropriate rotating speed, N  = 300 rpm, is selected in order to further study local hydrodynamic quantities using Particle Image Velocimetry (PIV), as well as mixing and mass transfer dynamics using Planar Laser-Induced Fluorescence (PLIF). The results obtained with these local experimental methods are analyzed in detail. Their averages are first successfully compared to global data. Statistical analysis of their spatial distributions show that large-scale flow patterns significantly influence mass transfer through the free-surface of the stirred tank. Even if global measurements show that global characteristic times for mixing and mass transfer differ by two orders of magnitude, local experimental characterization shows persistent vertical gradients of dissolved gas concentrations. So the dissolved gas concentration is not as perfectly uniform as one might expect.